2012
DOI: 10.1007/s00406-012-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired volitional saccade control: first evidence for a new candidate endophenotype in obsessive–compulsive disorder

Abstract: Recent research suggests that patients with obsessive-compulsive disorder (OCD) have deficits in the volitional control of saccades. Specific evidence comes from increased latencies of saccadic eye movements when they were volitionally executed but not when they were visually guided. The present study sought to test whether this deviance represents a cognitive endophenotype. To this end, first-degree relatives of OCD patients as genetic risk carriers were compared with OCD patients and healthy controls without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
4
16
1
2
Order By: Relevance
“…Kloft and colleagues56 investigated 22 unmedicated patients with OCD, 22 unaffected first-degree relatives of OCD patients, and 22 healthy volunteers. The study involved four task types: visually guided saccades and three different types of volitional saccade task: cued, un-cued, and free choice.…”
Section: Saccadic Movements and Psychiatric Disorders: Resultsmentioning
confidence: 99%
“…Kloft and colleagues56 investigated 22 unmedicated patients with OCD, 22 unaffected first-degree relatives of OCD patients, and 22 healthy volunteers. The study involved four task types: visually guided saccades and three different types of volitional saccade task: cued, un-cued, and free choice.…”
Section: Saccadic Movements and Psychiatric Disorders: Resultsmentioning
confidence: 99%
“…The first research that adopted this approach showed that OCD patients and their UFDR had deficits in motor inhibition (Chamberlain et al, 2007). Similar studies also found impairments in planning and working memory processes (Delorme et al, 2007), cognitive flexibility (Cavedini et al, 2010), volitional action generation (Kloft et al, 2013), performance monitoring (Riesel et al, 2011) and behavioral reversal (Viswanath et al, 2009) presented in both OCD probands and their UFDR. Moreover, to remove the effect of the drug treatment, a study by Rajender et al (2011) reported impaired set-shifting and inhibitory control in patients with drug-naïve OCD and their UFDR.…”
Section: Introductionmentioning
confidence: 90%
“…Because of feasible impaired volitional saccade control in patients with obsessive-compulsive disorder (OCD), Kloft et al [5] hypothesized this deviance to be a cognitive endophenotype. They compared 22 unaffected first-degree relatives of OCD patients as genetic risk carriers to 22 unmedicated OCD patients and 22 healthy controls without such family history.…”
mentioning
confidence: 99%